Self‐efficacy, sympathy, and attributions: Understanding helping intentions towards disclosers of mental health concerns on social media. Issue 4 (7th November 2022) - White, Jessica; Ahern, Elayne
Abstract: Mental health disclosures increasingly occur on online platforms. In a moderated‐mediation analysis, we assessed an adapted Corrigan's attribution model (2003) including factors such as the sincerity of online disclosure and support self‐efficacy to predict helping intentions on social media. Participants ( N = 177) were randomly allocated to one of three conditions and presented with a social media vignette experimentally manipulating controllability attributions (low, high, neutral controllability). Participants completed controllability, sincerity, sympathy, self‐efficacy, and helping intentions questionnaires. While preliminary exploratory analyses revealed that the proposed model significantly explained helping intentions, the proposed mechanisms of serial‐mediation via sincerity of disclosure and sympathy was not supported, nor was this dependent on self‐efficacy. Nonetheless, sympathy and self‐efficacy uniquely and significantly explained helping intentions. Thus, an intervention that upskills individuals in online support provision offers promise in terms of accessible, online, community‐based treatment initiatives.